Kesiapan Pengguna Digital Banking Terhadap Transformasi Sistem Akuntansi Berbasis Blockchain: Studi Kasus Pada Mahasiswa Perguruan Tinggi Negeri di Daerah Istimewa Yogyakarta - Daniel Bangkit Cahyo Dewanto; Dian Indri Purnamasari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The development of blockchain technology has driven the transformation of accounting systems in the banking industry, particularly through digital banking services. However, user readiness remains a major challenge in the adoption process. Therefore, this study aims to analyse the factors that influence user readiness in adopting blockchain technology. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was used as an approach to identify factors that influence users' intentions to adopt blockchain-based accounting systems. This study used a quantitative survey method. Data were collected through a Likert scale questionnaire distributed to students who are digital banking users in the Special Region of Yogyakarta. A total of 139 respondent data were analysed using multiple linear regression with the help of SPSS version 26. The results showed that performance expectancy, effort expectancy, social influence, and facilitating conditions had a positive and significant effect on the behavioural intention of blockchain-based digital banking users. These findings indicate that perceived benefits, ease of use, social influence, and infrastructure support are important factors in increasing users' readiness and interest in adopting blockchain technology in banking accounting systems. This indicates that the higher the perceived benefits and ease of use of the technology, and the stronger the social influence and infrastructure support available, the greater the readiness and intention of users to adopt blockchain technology. These findings confirm that user readiness is a key factor in supporting the successful transformation of blockchain-based banking accounting systems.